Implementing IT security penetration testing in higher education institute: A case of University Teknologi MARA (UiTM) Pahang / Zulazeze Sahri …[et al.] - Sahri, Zulazeze; Abdul Malek, Mohamad Affendi; Abd Aziz, Muhd Eizan Shafiq; Jamaludin, Roslan; Canda, Roger (2013)
The higher educational industry has unique information security requirements as the organization holds critical data and information of students, employees, research findings as well as other university's main agenda information. This paper proposed an enhanced process flow for web deployment by implementing IT security penetration testing practices in University Teknologi MARA (UiTM) Pahang, Campus Jengka, as a way to early detection, reduce and prevent the institution's information security and services. This empirical research is based on qualitative data analysis which applied action research and interviews that requires researcher to study the existing university's IT security policy, infrastructure and available services. The development of the penetration testing process flow is guided by various industry standard penetration testing frameworks and literature review.